TRADISI DAKWAH ULAMA AL JAM’IYATUL WASHLIYAH SUMATERA UTARA - Muhammad Rozali (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2016)
Al Jam'iyatul Washliyah an Islamic organization that was born and raised in North Sumatra at 1930. One of the activities of Al Washliyah in educating the public are with da’wah. So far Al Washliyah contribute for the development of Islamic da’wah in the region, it can be seen from the number of educational institutions Al Washliyah spread in North Sumatra from the lowest to the highest. So far the activities are still relevant in the community and his presence are still needed, especially the tradition of da’wah, with the arguments. First, Al Jam’iyatul Washliyah maintains its tradition in education consist with the ideals of its founders. Second, Al Jam’iyatul Washliyah provides educational institutions, dakwah, social and economic opportunity as a source of life for it’s members. Third, The existence of Al Jam’iyatul Washliyah able to raise the level of the religious understanding of the community.